PENINGKATAN MINAT DAN HASIL BELAJAR SISWA MELALUI PROBLEM BASED LEARNING DENGAN BLOCKLY DAN GOOGLE SITES PADA MATA PELAJARAN INFORMATIKA KELAS VIID DI SMP NEGERI 7 MALANG - Ulum, Khoirul; Irianto, Wahyu Sakti Gunawan; Wardhana, Nyoman Dedi Kusuma; Hasriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve students' interest and learning outcomes in Informatics subjects through the implementation of project-based learning with Blockly and Google Sites. The subjects of the study were students of class VIID of SMP Negeri 7 Malang. The research method used was classroom action research (CAR) with two cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The results of this study indicate that the implementation of project-based learning through Blockly and Google Sites can improve students' interest in learning, as indicated by an increase in active participation, enthusiasm, and motivation of students during the learning process. In addition, student learning outcomes also showed a significant increase, marked by an increase in the average final test score in each cycle. This study is based on constructivism theory, which highlights the importance of students' roles in the educational process, as well as previous research that has shown the effectiveness of project-based learning methods in improving students' skills and understanding. Therefore, the use of project-based learning methods involving technology such as Blockly and Google Sites can be considered an effective alternative to improve the quality of education in Informatics.